Overview of Epidemiology and Contribution of Obesity and Body Fat Distribution to Cardiovascular Disease: An Update - Piché, Marie-Eve; Poirier, Paul; Lemieux, Isabelle; Després, Jean-Pierre (Progress in cardiovascular diseases, 2018)
Obesity is recognized as a heterogeneous condition in which individuals with similar body mass index may have distinct metabolic and cardiovascular risk profiles. Susceptibility to obesity-related cardiometabolic complications is not solely mediated by overall body fat mass, but is largely dependent upon individual differences in regional body fat distribution and ability of subcutaneous adipose tissue to expand. The present review will discuss to what extent the individual variation in body fat distribution is one of the clinical key variables explaining the metabolic heterogeneity of obesity and its related cardiovascular risk. We will present the evidence for the complex nature of the relationship between obesity and cardiovascular disease, outline our current understanding of the mechanisms involved, and identify future direction of research pertinent to this interaction.